Perfecting A Video Game with Game Metrics - Junaidi Junaidi; Andy Julianto; Nizirwan Anwar; Safrizal Safrizal; Harco Leslie Hendric Spits Warnars; Kiyota Hashimoto (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
A state of a perfect video game is what developers has been seeking for their product developments, to achieve the selected state, several standards and methods needs to be applied. These standards and methods are special: they are both verifiable and quantifiable, to make their action and end goal a clear one, the terms for this standards and methods are called ‘game metrics’ and we decided that this is a must-have tool or method to be implanted in a development of a game because it will boost your standards rapidly and will be able to tell you about your own progress of the development.